2022
DOI: 10.3390/rs14133022
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Aboveground Carbon Density of Forests Using Deep Learning and Multisource Remote Sensing

Abstract: Forests are crucial in carbon sequestration and oxygen release. An accurate assessment of forest carbon storage is meaningful for Chinese cities to achieve carbon peak and carbon neutrality. For an accurate estimation of regional-scale forest aboveground carbon density, this study applied a Sentinel-2 multispectral instrument (MSI), Advanced Land Observing Satellite 2 (ALOS-2) L-band, and Sentinel-1 C-band synthetic aperture radar (SAR) to estimate and map the forest carbon density. Considering the forest fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The present study is in accordance with the report by [ 63 , 64 ], which proposed that landscape plants with functional carbon sequestration and oxygen release can exchange more CO 2 and O 2 with the external environment, then transform more solar energy into organic matter stored in plants. It is known that all the principal biotic components of carbon sequestration and oxygen release stem from the photosynthetic process of plants [ 21 , 65 ]. With the increase in Cd treatment concentration, P , W CO 2 , W O 2 , P CO 2 and P O 2 in L. japonica began to decrease; however, when Cd treatment concentration was up to 125 mg kg −1 , P , W CO 2 , W O 2 , P CO 2 and P O 2 in L. japonica had no significant decrease compared with the control, which indicated a good photosynthetic ability of the plant even under high concentrations of Cd treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The present study is in accordance with the report by [ 63 , 64 ], which proposed that landscape plants with functional carbon sequestration and oxygen release can exchange more CO 2 and O 2 with the external environment, then transform more solar energy into organic matter stored in plants. It is known that all the principal biotic components of carbon sequestration and oxygen release stem from the photosynthetic process of plants [ 21 , 65 ]. With the increase in Cd treatment concentration, P , W CO 2 , W O 2 , P CO 2 and P O 2 in L. japonica began to decrease; however, when Cd treatment concentration was up to 125 mg kg −1 , P , W CO 2 , W O 2 , P CO 2 and P O 2 in L. japonica had no significant decrease compared with the control, which indicated a good photosynthetic ability of the plant even under high concentrations of Cd treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of current advancements, our research distinguishes itself by offering a holistic evaluation of carbon stocks, encompassing both below-and above-ground reserves. This approach is in contrast to studies that typically emphasize aboveground biomass [35]. Our work advances the field by employing precise species-specific identification, thereby enhancing the granularity of carbon dynamic analysis.…”
Section: Enhancing Carbon Sequestration Assessment: Comparing Landsca...mentioning
confidence: 99%
“…Tang et al (2021) also showed the RF model was superior to SVM, PLSR and back-propagation artificial neural network (BP-ANN) in AGB monitoring of the headwater of the Yellow River grasslands. Some recent comparison studies on AGB estimation performance of DL and ML models suggested CNN algorithm was found to perform better than classical ML models (i.e., RF, SVM), due to CNN was more sensitive to changes in features (Du et al, 2021;Zhang et al, 2022). While another case study showed RF would obtain slightly better accuracy than CNN if the data was elaborately designed (Dong et al, 2020).…”
Section: Model Performances and Variables Selectionmentioning
confidence: 99%